Influence of Urban Sprawl on Spatial-Temporal Changes Along Rupingazi Riverine Ecosystem, Embu County, Kenya - Riungu, James Muthomi; Njeru, Moses Kathuri; Nkoroi, Medrine Cirindi (PT. Pubsains Nur Cendekia, 2026)
Urban sprawl refers to the unplanned expansion of urban areas, typically leading to inefficient land use and environmental degradation. This study analyzes the impact of urban sprawl on the Rupingazi River ecosystem between 1989 and 2019 using Landsat satellite imagery. Analysis of NDBI values revealed a consistent distinction between built-up and non-built-up areas, with built-up surfaces recording higher positive values across all periods. The findings show a significant transformation within Embu County. In 1989, non-built-up land and vegetation dominated the landscape at 4.7 km2 (70.47%). By 1999, this declined to 4.46 km2 (56.89%) as built-up areas expanded to 3.38 km2 (43.11%). A critical shift occurred in 2009, when built-up areas (4.58 km2; 51.93%) overtook natural cover (48.07%) for the first time. By 2019, urban surfaces reached 6.04 km2 (68.17%), leaving only 31.83% natural cover. These trends necessitate stricter zoning enforcement, riparian buffer protection, and compact development strategies. Urban planners must integrate geospatial monitoring to mitigate environmental pressure on the Rupingazi riverine ecosystem.